PERUMUSAN STRATEGI PENGEMBANGAN MARKISA (Passiflora edulis) ORGANIK UNTUK PASAR EKSPOR DI KELURAHAN BEJI KECAMATAN NGUNTORONADI KABUPATEN WONOGIRI - Nugroho, Suzain Sri; Wardani, Irma; Solikah, Umi Nur (Universitas Islam Kadiri, 2026)
The natural resource potential that can be developed in Nguntoronadi District is the development of tourism areas based on the agricultural sector. Beji Village is a village that develops organic passion fruit. The aim of this research is to determine and analyze internal and external factors and formulate a passion fruit development strategy in Beji Village. The basic research method used is a qualitative method. The location determination for this research was carried out purposively, namely in Beji Organic Village. Data methods were carried by observation, questionnaires and interviews. The data analysis used is using the IFE Matrix, EFE Matrix, SWOT Analysis and QSPM. EFE Analysis of Organic Passion Fruit (Passiflora Edulis) Development for the Export Market in Beji Village is 3.50 while the EFE is 2.53. From the combination of SWOT analysis and IFE and EFE matrices, the strategy choices that can be used include market development, market penetration and product development. The alternative strategy chosen is market development with a QSPM score of 6.96. Product development strategies that can be implemented are 1) making derivatives from passion fruit, 2) creating a village-specific e-commerce to market passion fruit online, 3) applying for funding to support developing passion fruit in Beji Village